Rancang Bangun Aplikasi Katalog Tumbuhan Angiospermae di UIN Sunan Kalijaga sebagai Media Pembelajaran - Farid Amrulloh, Mohamad Fajar; Handayani, Rika; Widodo, Widodo (BIO-EDU: Jurnal Pendidikan Biologi, 2024)
This research aims to design an Angiosperm plant catalog application as an effort to provide learning media to support biology learning in recognizing Angiosperm plants. This study uses a 3D development model, namely define, design, and development. The define stage is carried out using the field needs survey method. The design stage is carried out by designing an Angiosperm plant catalog application. The develop stage is carried out with validation tests and application usage tests. Application design is carried out by creating activity diagrams, interface designs, and designs using Android Studio. The final stage of application design is checking navigation, performance, and operations. The application is validated by material experts and media experts, and tested for use by peer reviewers, teachers, and students. The average results of the angiosperm plant catalog application product assessment were 86.36% with very good quality by 2 material experts, 85.7% with very good quality by 2 media experts, 95.14% with very good quality by 10 peer reviewers, 90.76% with very good quality by 2 biology teachers, and 85.2% with very good quality by 25 students of MAN 2 Yogyakarta.